William De Courcy papers - De Courcy, William, 1703-1769.
Correspondence, legal testimonies, wills, and petitions advanced in support of De Courcy's claim (1763) to the earldom of Kinsale and the barony of De Courcy in Ireland. Includes military resignation (1778 August 5) of Edward Coursey signed by Tench Tilghman and newspaper clipping (1871) concerning the true identity of Sir Roger Tichborne and his right to an inheritance of property in England.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Landowner.
Collection material in English.
Keywords: Coursey, Edward; Tilghman, Tench, -- 1744-1786.; Doughty-Tichborne, Roger Charles, -- 1829-1854.; Estates (Law) -- Great Britain; Titles of honor and nobility -- Great Britain; Wills; Ireland -- History -- 1558-1603.; Kinsale (Ireland) -- History; Wye River (Md.); Landowners